INTERCULTURAL COMMUNICATION: CULTURAL ACCULTURATION IN THE PENDALUNGAN COMMUNITY OF JEMBER REGENCY - Kartika Bina Kasih; Bunga Surawijaya Ningsih (International Conference on Humanity Education and Society (ICHES), 2023)
Since Jember was designated as an afdeling in 1883, it has resulted in a wave of multi-ethnic migration. Each ethnic or ethnic group is the Madurese and the Javanese are the majority ethnic group. They develop their own culture so that there is cultural acculturation called Pendalungan. Until now, they live side by side on the basis of their respective cultural differences, especially in the fields of art and language. Therefore, in writing this article aims to analyze cultural acculturation between Javanese and Madurese ethnic. This uniqueness is the main attraction of this new culture to be studied. Javanese culture and Madurese culture which merge into one and form a new culture give color to cultural diversity in Indonesia, and can only be found in Jember Regency. The method used is descriptive qualitative by utilizing relevant written sources. Based on the analysis, information was obtained that actually the Pendalungan culture still does not exist in Jember. Because by definition and cultural values, Pendalungan culture has not yet been formed. Because basically culture is created because of habits that are carried out successively and in the end it is used as an identity for a culture.